Metacognitive therapy for mathematics disorder. Issue 4 (February 2019) - Faradiba, S S; Sadijah, C; Parta, I N; Rahardjo, S
Abstract: Mathematical disorders are learning disabilities that greatly affect a person's mathematical abilities so that they need to be recognized as early as possible. This aims to minimize the negative impacts caused by mathematics disorder. This study is a descriptive qualitative research. The participants of this study were two university students of the department of mathematics education, Universitas Islam Malang. This paper describes Metacognitive therapy (MCT) for students who have mathematics disorder. MCT therapy is done by asking metacognitive questions which consist of comprehension, connection, strategic, and reflection questions. The purpose of MCT is to find out what students believe about their own thoughts and how their thoughts work about mathematics, then show students how this belief leads to an unsupported response to thoughts that inadvertently prolong or worsen symptoms, and ultimately give way alternative response to the mind to allow for symptom reduction. Need to be further investigated whether the results of metacognitive therapy are only temporary or not.